MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE TERHADAP MOTIVASI BELAJAR IPA SISWA SD - Julyanto, Ya' (Jurnal Pembelajaran Prospektif, 2021)
This research was motivated when the teacher delivered material tended to use conventional method (lectures) which resulted in students becoming bored. The models and strategies used in classroom learning to tend to be less attractive so that students' enthusiasm for learning decreases. As well as props/ media that are rarely used related to the material to be achieved so that students' motivation is less to participate in learning in thematic subjects, especiallyscience. This study aims to determine the effect of the example non example cooperative learning model on students' learning motivation in science subjects outside the body of plants and their function in Class IV SDN 06 Raut. This research uses Quasi experimental design or quasi experiment. While the design in this experimental study used the research design One group pre test and post test. And the method in this research is simple linear regression. Theresults of students' learning motivation in Science were obtained through analysis pretest and post test data, namely pretest (before) obtained an average of 53.95% while the post test data analysis (after) obtained an average of 56.3%. Based on the results of the study, it can be concluded that the use of the example non example cooperative learning model does not have an insignificant effect on the motivation to learn science in the material outside the body ofanimals and plants and its function in grade IV SDN 06 Raut.